2015
DOI: 10.1177/0145445515610744
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression in Bidirectional Relations Between Pain and Smoking

Abstract: Pain and tobacco smoking are highly prevalent and comorbid conditions that impose considerable burdens on individuals and health care systems. A recently proposed reciprocal model suggests that these conditions interact in a bidirectional manner, resulting in greater pain and the maintenance of tobacco addiction. Anxiety and depression are common among smokers in pain and have been identified as central mechanisms of interest. There is emerging evidence that smokers with anxiety/depression may experience more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 105 publications
(150 reference statements)
4
61
0
1
Order By: Relevance
“…Based on these data, we would hypothesize that as pain becomes increasingly linked with the self-administration of nicotine to ameliorate pain, the pain experience itself may gain salience as a conditioned interoceptive cue for tobacco smoking. Consistent with theoretical conceptualizations of allostatic load among chronic substance users [29; 30], smokers may become sensitized to the pain experience and evince greater pain reactivity (i.e., hyperalgesia) during the early stages of nicotine withdrawal, which in turn, could motivate relapse to smoking [15; 22; 70; 84]. …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Based on these data, we would hypothesize that as pain becomes increasingly linked with the self-administration of nicotine to ameliorate pain, the pain experience itself may gain salience as a conditioned interoceptive cue for tobacco smoking. Consistent with theoretical conceptualizations of allostatic load among chronic substance users [29; 30], smokers may become sensitized to the pain experience and evince greater pain reactivity (i.e., hyperalgesia) during the early stages of nicotine withdrawal, which in turn, could motivate relapse to smoking [15; 22; 70; 84]. …”
Section: Discussionmentioning
confidence: 90%
“…Chronic pain and tobacco addiction are both highly prevalent and comorbid disorders that likely interact in a bi-directional manner [22; 84]. Indeed, tobacco smoking has been identified as a unique risk factor in the development of chronic pain [72; 75], pain has been shown to motivate smoking behavior [20; 21], current smoking has been linked to more severe pain and functional impairment among treatment-seeking pain patients [33], and there is mounting evidence that pain may impede smoking cessation [24; 25; 83].…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco addiction and chronic pain are both highly prevalent and co-occurring disorders that have been hypothesized to operate in the manner of a positive feedback loop, resulting in greater pain and the maintenance of smoking behavior (Ditre, Brandon, Zale, & Meagher, 2011; Zale, Maisto, & Ditre, 2016). Rates of tobacco smoking among individuals in pain (28%–68%; Goesling, Brummett, & Hassett, 2012; Michna et al, 2004; Orhurhu, Pittelkow, & Hooten, 2015; Patterson et al, 2012) far exceed those observed in the general population (18%; CDC, 2014), and smokers with chronic pain (vs. no chronic pain) are nearly two times more likely to meet diagnostic criteria for nicotine dependence (Zvolensky, McMillan, Gonzalez, & Asmundson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Patients of low socioeconomic status are more likely to experience both acute and chronic pain, although some studies suggest that this link is better explained by psychological factors than by poverty‐related environmental risks (K. A. Davies et al, ). The link between mental health and chronic pain is well‐established throughout the literature: anxiety and depression increase the likelihood of chronic pain (Currie & Wang, ; Ohayon & Schatzberg, ; Zale, Maisto, & Ditre, ) and are associated with worse pain management (Bair, Robinson, Katon, & Kroenke, ; Dersh, Polatin, & Gatchel, ). Trauma exposure is a less‐established risk factor for chronic pain, as research findings have been mixed.…”
Section: Trauma Exposurementioning
confidence: 99%
“…Davies et al, 2009). The link between mental health and chronic pain is well-established throughout the literature: anxiety and depression increase the likelihood of chronic pain (Currie & Wang, 2004;Ohayon & Schatzberg, 2003;Zale, Maisto, & Ditre, 2016) and are associated with worse pain management (Bair, Robinson, Katon, & Kroenke, 2003;Dersh, Polatin, & Gatchel, 2002). Trauma exposure is a lessestablished risk factor for chronic pain, as research findings have been mixed.…”
Section: Physical Healthmentioning
confidence: 99%